Application of Information Technology to Education in the Age of the Fourth Industrial Revolution - Amitkumar Dudhat; Ardi (International Transactions on Education Technology (ITEE), 2023)
The purpose of this study is to clarify the readiness and challenges of learning information technology, and the challenges of education in this fourth era in applying information technology to learning insights. That's it. As a driver of information technology for learning insights in Indonesia, Indonesia's willingness to face the challenges of the era 4th has made us a credible player in the field of education management to improve human resource management through education and analysts. The challenges of the fourth growth area will soon improve. Therefore, Indonesia's current educational administration policy prioritizes the use of digital technology and progress in educational informatics for her four-year-olds at all levels of education, especially in higher education institutions. Solutions that can be implemented include setting appropriate curricula and educational guidelines, preparing human resources to use information and communication technologies, optimizing student skills and personal development, and preparing for digital learning facilities and infrastructure.